The business of tourism - Holloway, J. Christopher. (Longman, 1998)
An introduction to tourism. The history of tourism. Tourism in the twentieth century. The economics of tourism. Tourist motivation and behavior. The structure and organisation of the travel and tourism industry. Passenger transport: the aviation industry. Waterborne passenger transport...